2019
DOI: 10.1080/13607863.2019.1603284
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national prevalence and factors associated with suicide ideation and attempts in older and young-and-middle age people

Abstract: https://repositorio.uam.es Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 42 publications
2
45
0
6
Order By: Relevance
“…A longitudinal study carried out in countries with high HDI found that high levels of feelings of loneliness are significantly correlated with suicidal ideation in adult population (29). This is in agreement with cross-sectional large sample in young-andmiddle age adults in Europe studies that have documented that higher isolation being female and with chronic health conditions are related to 12-month suicidal ideation (30). In this sense, The estimated regression coefficients appear first, followed by the standard deviations of the parameters calculated from of the variance using the stepwise method (step by step).…”
Section: Discussionsupporting
confidence: 90%
“…A longitudinal study carried out in countries with high HDI found that high levels of feelings of loneliness are significantly correlated with suicidal ideation in adult population (29). This is in agreement with cross-sectional large sample in young-andmiddle age adults in Europe studies that have documented that higher isolation being female and with chronic health conditions are related to 12-month suicidal ideation (30). In this sense, The estimated regression coefficients appear first, followed by the standard deviations of the parameters calculated from of the variance using the stepwise method (step by step).…”
Section: Discussionsupporting
confidence: 90%
“… 5 A global study found that the rates of SI and SA over 12 months were 2% and 0.5%, respectively. 9 Prevalence was as high as 1.81% for SI and 0.41% for SA during the economic crisis (from 2011 to 2012) in Spain. 10 In Asian populations, the lifetime prevalence of any SI among older people residing in Sri Lanka was 13.0% (11.7% to 14.3%) for men and 21.8% (20.3% to 23.2%) for women, with no significant difference between twins and nontwins.…”
Section: Introductionmentioning
confidence: 94%
“…11,13,14 Other studies have found that a low level of education, being widowed, living alone, being in a nursing home, having financial problems and disability were related to SI among older adults. 9,10 Having psychiatric disorders, especially anxiety disorder, increases the risk of SA. 15,16 Depressive disorders and depressive symptoms were the most influential predictors of SI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations